A miniaturized multicellular platform to mimic the 3D structure of the alveolar-capillary barrier - Licciardello, Michela; Traldi, Cecilia; Cicolini, Martina; Bertana, Valentina; Marasso, Simone Luigi; Cocuzza, Matteo; Tonda-Turo, Chiara; Ciardelli, Gianluca (Frontiers in Bioengineering and Biotechnology, 2024)
Several diseases affect the alveoli, and the efficacy of medical treatments and pharmaceutical therapies is hampered by the lack of pre-clinical models able to recreate in vitro the diseases. Microfluidic devices, mimicking the key structural and compositional features of the alveoli, offer several advantages to medium and high-throughput analysis of new candidate therapies.Here, we developed an alveolus-on-a-chip recapitulating the microanatomy of the physiological tissue by including the epithelium, the fibrous interstitial layer and the capillary endothelium.A PDMS device was obtained assembling a top layer and a bottom layer obtained by replica molding. A polycaprolactone/gelatin (PCL-Gel) electrospun membrane was included within the two layers supporting the seeding of three cell phenotypes. Epithelial cells were grown on a fibroblast-laden collagen hydrogel located on the top side of the PCL-Gel mats while endothelial cells were seeded on the basolateral side of the membrane. The innovative design of the microfluidic device allows to replicate both cell-cell and cell-extracellular matrix interactions according to the in vivo cell arrangement along with the establishment of physiologically relevant air-liquid interface conditions. Indeed, high cell viability was confirmed for up to 10 days and the formation of a tight endothelial and epithelial barrier was assessed by immunofluorescence assays.